Antibody response to sequential vaccination with cell culture, recombinant, or egg-based influenza vaccines among U.S. adults - Thomas G. Boyce; Min Z. Levine; David L. McClure; Jennifer P. King; Brendan Flannery; Huong Q. Nguyen; Edward A. Belongia (Taylor & Francis Group, 2024)
The immune response to inactivated influenza vaccines (IIV) is influenced by multiple factors, including hemagglutinin content and egg-based manufacturing. Only two US-licensed vaccines are manufactured without egg passage: cell culture-based inactivated vaccine (ccIIV) and recombinant vaccine (RIV). We conducted a randomized open-label trial in central Wisconsin during the 2018-19 and 2019-20 seasons to compare immunogenicity of sequential vaccination. Participants 18-64 years old were randomized 1:1:1 to receive RIV, ccIIV or IIV in strata defined by number of influenza vaccine doses in the prior 3 years. They were revaccinated with the same product in year two. Paired serum samples were tested by hemagglutination inhibition against egg-adapted and cell-grown vaccine viruses. Serologic endpoints included geometric mean titer (GMT), mean fold rise, and percent seroconversion. There were 373 participants randomized and vaccinated in 2018-19; 332 were revaccinated in 2019-20. In 2018-19, RIV and ccIIV were not more immunogenic than IIV against A/H1N1. The post-vaccination GMT against the cell-grown 3C.2a A/H3N2 vaccine virus was higher for RIV vs IIV (p = .001) and RIV vs ccIIV (p = .001). The antibody response to influenza B viruses was similar across study arms. In 2019-20, GMT against the cell-grown 3C.3a A/H3N2 vaccine virus was higher for RIV vs IIV (p = .03) and for RIV vs ccIIV (p = .001). RIV revaccination generated significantly greater backboosting to the antigenically distinct 3C.2a A/H3N2 virus (2018-19 vaccine strain) compared to ccIIV or IIV. This study adds to the evidence that RIV elicits a superior immunologic response against A/H3N2 viruses compared to other licensed influenza vaccine products.